Virtual reality cue exposure as an add-on to smoking cessation group therapy: a randomized controlled trial - A. M. Kroczek; B. Schröder; D. Rosenbaum; A. Mühleck; J. Diemer; A. Mühlberger; A. C. Ehlis; A. Batra (Addiction Science & Clinical Practice)
Abstract Background Cue exposure (CE) is used for relapse prevention as part of smoking cessation therapy to reduce the automatized response to smoking-related cues. Using CET in virtual reality (VR) is an approach to increase its efficacy by creating cost-efficient high-risk situations. The efficacy of VR-based CETs was compared to that of an unspecific relaxation intervention as an add-on to an established cognitive-behaviorally oriented smoking cessation group therapy (G-CBT). Methods N = 246 abstinence-motivated smokers were included in a two-armed randomized controlled trial (G-CBT with VR-CET vs. G-CBT with progressive muscle relaxation/PMR) with 1-, 3-, and 6-month follow-ups (measurements in 2018–2020). All smokers joined a well-established G-CBT smoking cessation program with six sessions with four additional sessions of either VR-based smoking cue exposure therapy (VR-CET) or four sessions of group-based PMR. The primary outcome was abstinence after 6 months according to the Russell Standard; secondary outcomes included changes in the number of smoked cigarettes, craving (assessed by the Questionnaire of Smoking Urges/QSU), and self-efficacy (assessed by the Smoking Abstinence Self-Efficacy Scale/SES) over time. Results Primary outcome: Six months after G-CBT, 24% of the participants were abstinent, and there was no significant difference between the PMR (n = 34/124) and VR-CET (n = 24/122) groups (odds ratio PMR/VR = 0.64). Secondary measures: SES increased, and QSU and the number of smoked cigarettes decreased over time. Baseline craving ratings predicted abstinence only in the VR-CET group. Conclusion This randomized controlled trial did not show increased abstinence rates related to smoking cue exposure in virtual reality. Secondary measures demonstrated significant reductions in craving and cigarette consumption as well as increases in self-efficacy over time, regardless of the intervention. However, high baseline craving was negatively related to abstinence in the VR-CET group, suggesting that intense craving was insufficiently addressed. This may indicate that the amount of training was insufficient and should be intensified. Individualization, e.g., adaptive, individualized approaches, is required to improve the effects of the VR-CET on smoking cessation in future studies. Trial registration ClinicalTrials.gov Identifier NCT03707106.